Prediction of three lipid derivatives for postoperative gastric cancer mortality: the Fujian prospective investigation of cancer (FIESTA) study - Hu, Dan; Peng, Feng; Lin, Xiandong; Chen, Gang; Liang, Binying; Chen, Ying; Li, Chao; Zhang, Hejun; Fan, Guohui; Xu, Guodong; Xia, Yan; Lin, Jinxiu; et al. (BMC cancer, 2018)
As we previously reported, the presence of preoperative metabolic syndrome can predict the significant risk of gastric cancer mortality. As a further extension, we evaluated the prediction of three lipid derivatives generated from triglycerides (TG), total cholesterol (TC), high- and low-density lipoprotein cholesterol (HDLC and LDLC) at baseline for postoperative gastric cancer mortality by prospectively analysing 3012 patients. The three lipid derivatives included the ratio of TC minus HDLC to HDLC known as atherogenic index (AI), the ratio of TG to HDLC abbreviated as THR and the ratio of LDLC to HDLC abbreviated as LHR. Gastric cancer patients who received gastrectomy between January 2000 and December 2010 were consecutively recruited from Fujian Cancer Hospital. Follow-up assessment was implemented annually before December 2015. Finally, there were 1331 deaths from gastric cancer and 1681 survivors, with a median follow-up time of 44.05 months. 3012 patients were evenly randomized into the derivation group and the validation group, and both groups were well balanced at baseline. Overall adjusted estimates in the derivation group were statistically significant for three lipid derivatives (hazard ratio [HR]: 1.20, 1.17 and 1.19 for AI, THR and LHR, respectively, all P < 0.001), and were reproducible in the validation group. The risk prediction of three lipid derivatives was more obvious in males than females, in patients with tumor-node-metastasis stage I-II than stage III-IV, in patients with intestinal-type than diffuse-type gastric cancer, in patients with normal weight than obesity, and in patients without hypertension than with hypertension, especially for AI and LHR, and all results were reproducible. Calibration and discrimination statistics showed good reclassification performance and predictive accuracy when separately adding three lipid derivatives to baseline risk model. A prognostic nomogram was accordingly built based on significant attributes to facilitate risk assessment, with a good prediction capability. Our results indicate that preoperative lipid derivatives, especially AI and LHR, are powerful predictors of postoperative gastric cancer mortality, with more obvious prediction in patients of male gender or with tumor-node-metastasis stage I-II or intestinal-type gastric cancer, and in the absence of obesity or hypertension before gastrectomy.